A method and system for providing and managing information of prefabricated construction components between manufacturers and architects - Ibrahim, Rahinah; Abdullah, Rusli; Jaafar, Mohd Saleh; Mamdooh, Maziyar (2011)
The present invention discloses a method (100) for providing and managing information of prefabricated construction components between manufacturers and architects to be used into architectural modular design processes. The manufacturer's product information relating to various prefabricated construction components are aggregated (101). A unique code is assigned to each prefabricated construction component (103) by synthesising product information of the prefabricated construction component into coding syntaxes and stored into a database (105). the product information in the format of the unique codes are then distributed on demand of architects for their architectural modular designs processes (107).